Paneleiras de Goiabeiras & paneleiros de Guarapari : limites e influências entre patrimônio cultural, artesanato e mercado - Muniz, Geysa Salmásio (2014)
This research aims to understand the relationship between craft, the intangible cultural heritage and the market, analyzing the influences of one over the other. To this end, we conducted a comparative case study between clay pot makers from Goiabeiras, w